2014
DOI: 10.1155/2014/291067
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Transcriptome Analysis of Male and Female Olive Flounder (Paralichthys olivaceus)

Abstract: Olive flounder (Paralichthys olivaceus) is an important commercially cultured marine flatfish in China, Korea, and Japan, of which female grows faster than male. In order to explore the molecular mechanism of flounder sex determination and development, we used RNA-seq technology to investigate transcriptomes of flounder gonads. This produced 22,253,217 and 19,777,841 qualified reads from ovary and testes, which were jointly assembled into 97,233 contigs. Among them, 23,223 contigs were mapped to known genes, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
49
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 51 publications
5
49
1
Order By: Relevance
“…Further, nothing is known about possible hidden alterations, particularly in the resistant females mentioned above, which exhibit an otherwise apparently normal ovarian morphology. Thus, to date, most gonadal transcriptomic studies have been focused on the sexrelated differences in adult gonads: Olive flounder (Paralichthys olivaceus; Fan et al, 2014); yellow catfish (Pelteobagrus fulvidraco; Lu et al, 2014); zebrafish (Small, Carney, Mo, Vannucci, & Jones, 2009;Sreenivasan et al, 2008). Few studies reported the influences of elevated temperature on the gonadal transcriptomes, one in zebrafish (Ribas, Liew, et al, 2017) and the other in the Nile tilapia (Sun et al, 2018).…”
mentioning
confidence: 99%
“…Further, nothing is known about possible hidden alterations, particularly in the resistant females mentioned above, which exhibit an otherwise apparently normal ovarian morphology. Thus, to date, most gonadal transcriptomic studies have been focused on the sexrelated differences in adult gonads: Olive flounder (Paralichthys olivaceus; Fan et al, 2014); yellow catfish (Pelteobagrus fulvidraco; Lu et al, 2014); zebrafish (Small, Carney, Mo, Vannucci, & Jones, 2009;Sreenivasan et al, 2008). Few studies reported the influences of elevated temperature on the gonadal transcriptomes, one in zebrafish (Ribas, Liew, et al, 2017) and the other in the Nile tilapia (Sun et al, 2018).…”
mentioning
confidence: 99%
“…Although N50 is not an exact parameter to measure the accuracy of contigs (Salzberg et al, 2012), it is one of the most popular reference-free measures (Li et al, 2014). The N50 value was in the range reported for other transcriptome de novo fish studies (Milano et al, 2011;Fan et al, 2014;Schunter et al, 2014). …”
Section: Resultsmentioning
confidence: 77%
“…Based on calculation criterion of FDR<0.05 and log2|FC|≧1, 38,167 unigenes showied signifcant expression difference between male and female individuals, including 5,892 (15.44%) male-biased unigenes and 942 (2.47%) female-biased unigenes ( Fig 6). According to our sequence analysis and other published search strategies [5], sex-related well-documented genes were identifed (Table 2). Obviously, many sex-linked genes, especially those located upstream of gonadal development regulatory network, had much more significant difference trend in expression levels, such as dmrt1, foxl2, cyp19a, and so on.…”
Section: Sex-related Genes Idetification From Comparison Of Gonad Tismentioning
confidence: 99%